Public Speaking Challenges Among EFL Learners: Evidence from an English Camp Experience - Amiruddin; Ines Darasinta (JURNAL ILMIAH MAHASISWA, 2026)
Public speaking in English presents significant challenges for EFL learners, particularly in Indonesian university contexts where opportunities for authentic oral communication remain limited. This study explores how university students navigate public speaking challenges through their participation in an English immersion camp. Using a qualitative approach with narrative inquiry design, data were collected through semi-structured interviews with six participants aged 21-23 years who had completed the Saree English Camp program in Aceh Besar, Indonesia. Thematic analysis was employed to examine participants' experiences before, during, and after the camp. The findings reveal that participants initially faced multidimensional challenges including psychological barriers (anxiety, fear of negative evaluation, low self-confidence), limited linguistic competence (vocabulary, pronunciation, grammar), and lack of supportive speaking environments. The English camp facilitated transformation through its immersive English-only environment, continuous speaking practice, and strong peer support, which collectively reduced anxiety, normalized mistakes, and increased confidence. Participants developed greater willingness to communicate, improved fluency, and more positive attitudes toward speaking English. However, sustaining these improvements post-camp remained challenging due to the absence of supportive English-speaking environments in daily life. This study contributes empirical insights into how immersive learning environments address both linguistic and psychological dimensions of public speaking development, while highlighting the need for sustained practice opportunities beyond intensive programs